A communal approach to sexual need responsiveness in romantic relationships. Issue 1 (1st January 2020) - Impett, Emily A.; Kim, James J.; Muise, Amy
ABSTRACT: Sex is a crucial factor that impacts the quality and stability of relationships, yet many couples report recurrent sexual issues – such as discrepancies in their desired sexual frequency or levels of sexual desire – that detract from their relationship quality. This article describes how applying the theory of communal motivation from relationship science to the sexual domain of relationships can shed light onto understanding how couples can maintain desire over time, remain satisfied in the face of conflicting sexual interests, and decline one another's sexual advances in ways that protect their relationship. We integrate a decade of research on communal motivation, sexual rejection, and responses to sexual rejection to provide a better, and more holistic, understanding of how partners can successfully balance their sexual needs to ultimately reap the powerful rewards of a fulfiling sexual connection.